Discussion of Accelerated Depreciation and Deferred Taxes: An Empirical Study of Fluctuating Asset Expenditures - Dyckman, Thomas R. (Journal of Accounting Research, 1967)
Thomas R. Dyckman, Discussion of Accelerated Depreciation and Deferred Taxes: An Empirical Study of Fluctuating Asset Expenditures, Journal of Accounting Research, Vol. 5, Empirical Research in Accounting: Selected Studies 1967 (1967), pp. 124-138